Effect of the Dosing Interval for Oral Dosage Regimens of Methotrexate on the Probability of Target Attainment in Rheumatoid Arthritis Patients using Monte Carlo Simulation - Pensomboon, Prapon; Charoenwong, Nichanan; Towiwat, Patapong; Sermsappasuk, Pakawadee (Journal of Basic and Applied Pharmacology, 2020)
Methotrexate (MTX) is commonly used to treat rheumatoid arthritis. The drug is usually orally administered once a week. Due to the problems with saturation of absorption and gastrointestinal intolerance, twice weekly oral administration and once weekly subcutaneous administration regimens are also used in clinical practice. However, the effects of different oral dosing intervals on trough concentration at steady state (Ctr,ss) and efficacy of the drug have not yet been studied. Our objective was to compare the probability of target attainment (PTA) among three twice weekly oral MTX dosage regimens with different dosing intervals (Saturday morning- evening, Saturday-Sunday and Saturday-Tuesday). A Monte Carlo simulation for prediction of MTX-polyglutamates (MTX-PGs) concentrations in red blood cells (RBC) of simulated patients was conducted using a population pharmacokinetic model of MTX in rheumatoid arthritis patients. Percent PTA for RBC MTX-PGs Ctr,ss of ³ 83 nmol/L (the lower limit of the therapeutic range) was calculated for each MTX regimen. Our results based on Monte Carlo simulation showed that, at oral doses ³ 20 mg/week, twice weekly administration resulted in notably higher Ctr,ss of MTX-PGs and %PTA than those of once weekly regimen. No difference in %PTA among the three tested twice weekly oral dosage regimens was observed; therefore, dosing interval was unlikely to affect MTX efficacy for twice weekly regimens. Nonetheless, further clinical studies are required to verify this simulated observation.